Paving Block from LDPE Plastic and Pyrolysis Residue - Lenny Marlinda (Jurnal IPTEK, 2022)
The purpose of this study was to utilize residues of the plastic waste pyrolysis process and LDPE plastic as a substitute of cement in the manufacture of paving blocks. The residual pyrolysis process used was a pyrolysis residue of a mixture of polypropylene (PP) and low density polyethylene (LDPE) plastic waste with mass ratio of 100% PP, 75: 25%, 50: 50%, 40: 60%, 25: 75, and 100% LDPE. The mass ratio of LDPE plastic and pyrolysis residue were 70:30%, 60:40%, and 50:50%. The comparison of sand and residual pyrolysis of plastic waste used was 1: 1. The block paving obtained was characterized using SEM and quality tests were carried out with parameters of compressive strength and water absorption. The results of SEM analysis indicate the existence of a bond between sand and plastic pyrolysis residues. The variations in the type of plastic ratio in pyrolysis process indicate the varying of compressive strength and water absorption of the paving blocks